Shedding Light on CO Oxidation Surface Chemistry on Single Pt Catalyst Nanoparticles Inside a Nanofluidic Model Pore - Albinsson, David (ACS Catal, 2021)
[Image: see text] Investigating a catalyst under relevant application conditions is experimentally challenging and parameters like reaction conditions in terms of temperature, pressure, and reactant mixing ratios, as well as catalyst design, may significantly impact the obtained experimental results. For Pt catalysts widely used for the oxidation of carbon monoxide, there is keen debate on the oxidation state of the surface at high temperatures and at/above atmospheric pressure, as well as on the most active surface state under these conditions. Here, we employ a nanoreactor in combination with single-particle plasmonic nanospectroscopy to investigate individual Pt catalyst nanoparticles localized inside a nanofluidic model pore during carbon monoxide oxidation at 2 bar in the 450–550 K temperature range. As a main finding, we demonstrate that our single-particle measurements effectively resolve a kinetic phase transition during the reaction and that each individual particle has a unique response. Based on spatially resolved measurements, we furthermore observe how reactant concentration gradients formed due to conversion inside the model pore give rise to position-dependent kinetic phase transitions of the individual particles. Finally, employing extensive electrodynamics simulations, we unravel the surface chemistry of the individual Pt nanoparticles as a function of reactant composition and find strongly temperature-dependent Pt-oxide formation and oxygen spillover to the SiO(2) support as the main processes. These results therefore support the existence of a Pt surface oxide in the regime of high catalyst activity and demonstrate the possibility to use plasmonic nanospectroscopy in combination with nanofluidics as a tool for in situ studies of individual catalyst particles.